Ontological and conceptual bases for a scientific knowledge model in biomedical articles - DOI: 10.3395/reciis.v3i1.240en - Carlos Henrique Marcondes; Marília Alvarenga Rocha Mendonça; Luciana Reis Malheiros; Leonardo Cruz da Costa; Tatiana Cristina Paredes Santos (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2009)
Scientific articles published in electronic format are knowledge bases, specially in Medicine. An obstacle to semantic processing of this knowledge by computers is that, in spite of their digital format, articles are in text format for human reading and processing. A model is proposed to electronic publishing scientific articles both in textual format and in machine "understandable" format, in ontology format. The model is based in insights from Philosophy and Methodology of Science and in the results of analysis of 75 scientific articles in Medicine. Software agents can process the content of an article thus enabling semantic retrieval, consistence checking and the identification of new discoveries.